UV-VISIBLE OPTICAL ABSORBANCE OF GRAPHENE OXIDE IN COPPER IONIC LIQUID SYNTHESIZED VIA ELECTROCHEMICAL METHOD ASSISTED BY A COPPER COIL - Wipsar Sunu Brams Dwandaru; Oktiana Lusi Priyani; Bagas Prakoso; Rhyko Irawan Wisnuwijaya; Iman Santoso; Arif Rahman (Spektra: Jurnal Fisika dan Aplikasinya, 2018)
An optical absorbance study using Ultraviolet-Visible (UV-Vis) spectrophotometer device has been conducted on graphene oxide (GO) in copper (Cu) ionic liquid using electrochemical exfoliation combined with a direct current (DC) electrical circuit of copper coil given inside the electrolyte solution. The electrolyte solutions used are sulfuric acid (H2SO4) and chloride acid (HCl). The UV-Vis spectrum of the samples shows absorbance peaks at around 214 nm to 218 nm and shouldering peaks around 245 nm to 249 nm. The first peak corresponds to the existence of copper (Cu) ionic liquid in the solution, whereas the shouldering peak is related to the occurrence of GO material. A comparison between UV-Vis spectral of graphite in dimethylformamide (DMF) and GO in Cu ionic liquid in DMF resulted in the existence of a blue shift which signifies the production of Cu ionic liquid from the Cu coils inside the electrolyte solution. Increasing the concentration of the solution increases the absorbance peaks. Furthermore, raising the number of loops yields in the increase of the absorbance value at the first peaks that show Cu ionic liquid, but tends to decrease the absorbance value of the shouldering peaks of the GO material.